Perlindungan Hukum Internasional Bagi Pasukan Penjaga Perdamaian Perserikatan Bangsa-Bangsa - Felix Mayaut; Lucia Charlota Octovina Tahamata; Wilshen Leatemia (Faculty of Law Pattimura University, 2022)
Introduction: Peacekeeping Forces are troops formed by the Security Council to maintain international. These troops are usually deployed after a conflict in a country and have obtained prior agreement with the disputing parties.Purposes of the Research: This writing aims to understand and find out the forms of protection and legal status of the UN peacekeepers. Methods of the Research: The research method in this paper uses a descriptive analytical research type. The research approach used is a law approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, documents, scientific works of legal scholars, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Results of the Research: The results show that the form of protection for peacekeepers in armed conflict is regulated in the 1949 Geneva Conventions and the 1994 United Nations Personnel Safety Convention. Neither personnel, equipment and buildings may be subjected to attacks or actions that prevent them from carrying out their mandate. MONUSCO's legal status is contained in Security Council Resolution 2556 of 2020 and the Status of Force Agreement which describes their duties, functions and privileges in a country. Attacks against them in any form are punished according to their severity and the United Nations as the mandate giver has the right to file claims for damages suffered while carrying out official obligations as representatives of the United Nations, based on the Advisory Opinion of the International Court of Justice.